The Use of Ethnic-Cultural Educational Potential During the Acquaintance of Preschool Children with Nature - Valentyna Aleshko; Alla Brodovs’ka (Pedagogical Discourse, 2012)
The article deals with the problem of the acquaintance of preschool children with nature. It pays attention to the use of ethnic-cultural educational potential in the formation of a personality and the use of folk nature study traditions during the acquaintance of preschool children with nature.